Discovery of a Chemical Probe to Study Implications of BPTF Bromodomain Inhibition in Cellular and in vivo Experiments. (6th February 2023) - Martinelli, Paola; Schaaf, Otmar; Mantoulidis, Andreas; Martin, Laetitia J.; Fuchs, Julian E.; Bader, Gerd; Gollner, Andreas; Wolkerstorfer, Bernhard; Rogers, Catherine; Balıkçı, Esra; Lipp, Jesse J.; Mischerikow, Nikolai; et al.
Abstract: The bromodomain and PHD‐finger containing transcription factor (BPTF) is part of the nucleosome remodeling factor (NURF) complex and has been implicated in multiple cancer types. Here, we report the discovery of a potent and selective chemical probe targeting the bromodomain of BPTF with an attractive pharmacokinetic profile enabling cellular and in vivo experiments in mice. Microarray‐based transcriptomics in presence of the probe in two lung cancer cell lines revealed only minor effects on the transcriptome. Profiling against a panel of cancer cell lines revealed that the antiproliferative effect does not correlate with BPTF dependency score in depletion screens. Both observations and the multi‐domain architecture of BPTF suggest that depleting the protein by proteolysis targeting chimeras (PROTACs) could be a promising strategy to target cancer cell proliferation. We envision that the presented chemical probe and the related negative control will enable the research community to further explore scientific hypotheses with respect to BPTF bromodomain inhibition. Abstract : Unraveling the complex role of BPTF : Herein we report the discovery of BI‐7190, a potent and selective chemical probe targeting the bromodomain of BPTF with an attractive pharmacokinetic profile enabling cellular and in vivo experiments in mice.